Desain and Build a Medium Voltage Cubicel Temperature and Humidity Optimization Tool to Minimize the Occurrence of Corona Disease with the PLC-Based Fuzzy Method - Sindy Yurisma Sheila; Nur Wakhidatur Rochamwati; Faris Riyadi; Reza Fardiyan As’ad; Anggara Trisna Nugraha (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Cubicle is an electrical device that functions as a breaker, protector, connector, controller, and divider of the power system electricity from a power source and reduce sparks when connecting. One of the problems that occur in medium voltage cubicles is the presence of corona. Corona phenomena at cubicle terminations can trigger disturbances such as a decrease in insulation quality, power loss and a significant increase in harmonic distortion. Based on previous research, the solution to minimize the occurrence of corona is to optimize the temperature and humidity of the cubicle. Many of the previous studies examined the control of cubicle temperature and humidity using fans and heaters, but the temperature and humidity had not yet reached a stable and optimal point. In this study, raised a problem regarding the optimization of temperature and humidity in cubicles using the fuzzy method to stabilize the performance of medium voltage cells. In this study, it was found that the fuzzy method in this prototype was able to stabilize the panel humidity at 55% RH and stabilize the panel room temperature at 31.5 o C. Thus, it is hoped that a stable and optimal temperature and humidity can minimize the occurrence of corona. The use of HMI/SCADA based applications can facilitate the ability of the user (operator) to monitor several available parameters and manually control the operation of the panel (on/off).